Research recast(ed): S2E15 - Research creation and beak disorder with Leslie Sharpe - Miskiman, Megan; Schabert, Reinette; Sharpe, Leslie (My University, 2023)
In today’s episode, associate professor in Fine Arts here at MacEwan, Leslie Sharpe, discusses her research-creation involving sound, video, and other installation work related to climate change.
Keywords: installation art; climate change